Kinerja Belanja Daerah Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kota Bandung - Cecep Wahyu Hoerudin; Bayu Eka Lesmana; Wilda Fatimah (Publica: Jurnal Pemikiran Administrasi Negara, 2018)
This research was conducted to analyze the performance of spending at the Office of Investment and One Stop Integrated Services (DPMPTSP) of Bandung City in 2013-2017. The analysis of expenditure performance carried out in the study includes: analysis of shopping variance, shopping harmony, expenditure growth and expenditure efficiency ratios that can be a measurement tool in budget realization effectively, efficiently and economically. This research is in the form of descriptive qualitative. The data used is the budget realization report and the results of interviews conducted by researchers. Based on the results of the study, showed that (1) there was a saving in spending and categorized as quite good shopping performance, (2) expenditure growth in 2013-2017 could be said being quite volatile. Expenditure growth in 2013-2016 experienced positive growth while in 2017 experienced negative growth of -13.09% due to inflation, (3) the harmony of spending in 2013-2017 can be said to be the absence of budget harmonization in expenditure, (4) the ratio of expenditure efficiency in 2013-2017 already efficient enough, this is proven by the efficiency ratio of less than 100%.